แนวทางการพัฒนาอาชีพทอผ้าของชาวไทลื้อ บ้านแม่สาบ อำเภอสะเมิง จังหวัดเชียงใหม่ - ธนวัฒน์ ยวงสุวรรณ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The purpose of this study is searching for way to Thai Lue’s Textile Development Guidelines, Ban Mae Sap, Samoeng District, Chiang Mai Province Information Was given by 5 village leads and 10 elder in the village who has more than 30 years’ experience of wearing. All data by interview and present by the description. Result of study showed that the history of Thai Lue’s Textile Development Guidelines, Ban Mae Sap, Samoeng District, Chiang Mai Province is from the union of weaving in the past. The group was established in 1999, then the group has joined “One Tumbon, One Product” project and get 2 stars level. The Thai Lue tracery has the inspiration from nature, surrounding and belief in Buddhism. Product will be sold in the local market. The income will be collected for other use in group and Share to member. Afterward, the group get help from government organization such as the Community Development Dept, Samoeng pittayakhom school, the District cultural center and the province Cultural Center to promote product at “Wieng Ta Karn” The way to Thai Lue’s Textile Development Guidelines, Ban Mae Sap, Samoeng District, Chiang Mai Province.To develop Thai Luawearing, ThaiLue’s people should produce a various product and up to date with the market place, the package should be more modern and attract. The government organization must usually give suggestion and more help. Moreover, ThaiLue’s people should go other place for new idea, attentiveness to develop their career permanently. 25565101299765จ 00จ